P081 The application of multiomics to investigate the evolution of inflammatory bowel disease in pediatric and adult patients. (30th January 2023) - Maccalli, C; Gupta, I; Toufiq, M; Habib, T; Mathew, R; Shobha Manjunath, H; Missous, G N; Mifsud, W; Charles, A; Ammar, A A; Tomei, S; van Panhuys, N; et al.
Abstract: Background: The aim of this study is to monitor the evolution of Inflammatory Bowel Disease (IBD), including Crohn's Disease (CD) and Ulcerative Colitis through the integration of genomic and immunological investigations to assess the mechanisms of IBD severity and the risk to develop malignancy Methods: The study included pediatric (N=20) and adult (N=18) IBD patients at different stages of the disease (remission, mild, moderate and severe) and CRC patients with IBD history (N=13). Retrospectively collected tissues of IBD, inflamed non-IBD and normal gut tissues (N=10) were also utilized. Gut tissue biopsies (from both left and right side) and peripheral blood were collected from patients. DNA and RNA were extracted from fresh small size (2 mm in diameter) of gut tissues using the BioMasher II (Kimble) and All Prep DNA/RNA kits (Qiagen). Multiomics approach including MicroRNA (miRNA; N=700) and gene expression (N=800 genes) profiling were performed (cCounter platform; Nanostring) as well as the methylation profiling microarray (Infinium Methylation Epic Bead Chip kit, Illumina) to interrogate up to 850, 000 methylation sites across the genome. These analyses were coped with immunological investigations. See Figure 1. Results: Differential miRNA (such as miRNA92a-3p, 135-5p, 152-3p, 612; p<0.05) and gene signatures were found by the comparison of tissues from pediatric and adult patients with different stages of the disease. The differentially expressed genes belong to molecular pathways of inflammation, stemness, fibrosis, cell proliferation and migration (representative genes are: STAT3, CXCL2, MPM1, BIRC3, ISG15, ISG20, PECAM1). Pathways associated with the development of malignancy, such as PI3K/Akt/STAT and Wnt/GSK-3b were also detected as significantly differentially expressed. Differential profiles were also detected when comparing biopsies collected from right and left sides of gut in both pediatric and adult patients. Methylation sites at single nucleotide resolution have been also analyzed and correlated with miRNA and gene expression profiles Conclusion: Although the results are currently under further investigation, the ongoing integration of data from multiple platforms provide insights of the overall molecular determinants in IBD patients along with the evolution of the disease and the clinical outcome